Effect of ferromagnetic paste on insulating properties of transformer oil - I. Y. Bragin; L. A. Panteleeva; P. N. Pokoev; E. I. Gracheva (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Consider the problem of using a special ferromagnetic paste, which fills the air gaps in the magnetic circuit of an oil power transformer, in order to reduce its losses, by reducing eddy currents in the magnetic circuit. Conduct experiments to determine the dynamics of change of high-voltage breakdown of transformer oil, after adding ferromagnetic paste to it.METHODS. To solve this problem, several samples of ferromagnetic paste have been developed, differing from each other using different binding material for ferromagnetic powder. The samples were placed in containers for several days filled with transformer oil. With the help of electrical installation AIM-90, measurements of high-voltage breakdown of transformer oil of each sample were carried out. Thanks to this method, it was possible to determine how the ferromagnetic paste affects the insulating properties of the transformer oil. RESULTS. For clarity, the results of all samples were plotted. Based on the graph, it became clear that in some samples of transformer oil a significant amount of mechanical impurities formed from ferromagnetic paste appeared, which extremely negatively affected the insulating properties of the oil. There were also samples in which the properties of the oil practically did not change. CONCLUSION. As conclusions, there was a certain vision of which ferromagnetic paste can be used in the design of an oil power transformer, it was also possible to understand which samples of ferromagnetic pastes extremely negatively affect the insulating properties of the transformer oil.